2011
DOI: 10.4028/www.scientific.net/amm.109.290
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Vulnerability Analysis of Water Pipeline in Wenchuan Earthquake

Abstract: The seismic damage and loss of service of pipeline engineering may have great influence on the society, so the seismic research of pipeline engineering had always been highly valued. In this paper, the seismic damage characteristics of pipeline and vulnerability of water pipeline system in Wenchuan earthquake are analyzed, some revelations have been presented. The seismic capacity of pipeline engineering in some towns and cities was not adequate, the pipeline systems suffered great losses in Wenchuan Earthquak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…They used GIRAFFE software to establish the corresponding seismic model for the water supply system and calculated the seismic reliability of important water consumption nodes in the water supply system. Based on the research results obtained by Toprak [25], Adachi [26], Mahmood [27] and Guo [28], Halfaya [29] evaluated the water supply capacity of the water supply system after an earthquake by analysing the size, characteristics and joint form of the pipeline. The research results showed that pipelines should be arranged using the frequency and intensity of earthquakes occurring in the region as criteria.…”
Section: Analysis Of Key Issues In the Meaning Of Resiliencementioning
confidence: 99%
“…They used GIRAFFE software to establish the corresponding seismic model for the water supply system and calculated the seismic reliability of important water consumption nodes in the water supply system. Based on the research results obtained by Toprak [25], Adachi [26], Mahmood [27] and Guo [28], Halfaya [29] evaluated the water supply capacity of the water supply system after an earthquake by analysing the size, characteristics and joint form of the pipeline. The research results showed that pipelines should be arranged using the frequency and intensity of earthquakes occurring in the region as criteria.…”
Section: Analysis Of Key Issues In the Meaning Of Resiliencementioning
confidence: 99%
“…Among them, buried pipelines were always severely damaged in every historical great earthquake [1][2][3][4][5][6]. Damage and disruption of buried pipelines may cause detrimental effects on social life as it may lead to major economic losses [7].…”
Section: Introductionmentioning
confidence: 99%